(untitled) (Research, Society and Development, 2023)
Autologous breast reconstruction is of great importance for patients who need improvement in their breast shape, such as in patients after mastectomies. Several forms of flap are used for breast reconstruction, but the most used are the Inferior Epigastric Artery Perforator (DIEP), Transverse Rectus Abdominal Muscle (TRAM) and Latissimus Dorsal (LD). Under this analysis, due to its importance in the quality of life of patients, it is necessary to understand the literary evidence about the characteristics of the main flaps of the breasts. Therefore, the objective of the present study is to evaluate the use of the DIEP, TRAM and LD flaps in autologous breast reconstruction. This is an integrative literature review carried out in the PUBMED and MEDLINE databases in which the descriptors “Mammaplasty AND Transplantation, Autologous” were used in DeCS/MeSH, identifying 151 articles, of which 20 met the criteria. Regarding the use of breast flaps, the most used ones have a low complication rate and are safe to perform. However, despite this, complications should be carefully observed because they are important and lead to possible loss of the flap and the need for a new surgical approach. Therefore, good postoperative surveillance can prevent complications, improving the aesthetic result and reducing costs with the management of postoperative comorbidities and improving the patient’s quality of life.